e-Portfolios enhancing students’ self-directed learning: A systematic review of influencing factors - Beckers, Jorrick; Dolmans, Diana; Van Merriënboer, Jeroen (Australasian Journal of Educational Technology, 2016)
e-Portfolios have become increasingly popular among educators as learning tools. Some research even shows that e-portfolios can be utilised to facilitate the development of skills for self-directed learning. Such skills include self-assessment of performance, formulation of learning goals, and selection of future tasks. However, it is not yet clear under which conditions e-portfolios optimally facilitate the development of these skills. We conducted a systematic review aimed at identifying and understanding influences on the development of self-directed learning with an e-portfolio. Inclusion criteria were used to select recent, high quality studies that focused on e-portfolios and reported an influence on self-directed learning. There were 17 articles that met the inclusion criteria. Institutional factors, curriculum factors, learning process factors, personal factors, and portfolio factors were identified. Portfolios are used most effectively when faculty development aimed at supervising self-directed learning skills development is provided, when the portfolio is integrated into the educational routine, when teachers coach students regularly, when scaffolding is applied to increase motivation, and when the portfolio is designed to facilitate at least goal-setting, task-analysis, plan implementation, and self-evaluation.